Drought limits large trees in African savannas with or without elephants. (17th October 2022) - Jones, Maggie M.; Fletcher, Robert; Kruger, Laurence; Monadjem, Ara; Simelane, Phumlile; McCleery, Robert
Abstract: Consumers, including megaherbivores and fire, are considered important limiting forces for woody plants and canopy closure in African savannas. However, climatic events like drought can also play a significant role in limiting trees and maintaining tree‐grass coexistence in savannas. The extent to which top‐down control (e.g. megaherbivores) and bottom‐up resource limitation through drought and competition interact to influence savanna tree mortality and woody structure is unclear. Here, we compared the change in the number of large trees before and after a severe drought in a savanna with elephants ( Loxodonta africana ) and one without elephants. Elephants and drought both limited the number of large trees at our sites, but contrary to our predictions, there was no interactive effect of these drivers on overall changes in tree densities. However, there was a synergistic effect on the dominant tree species, Senegalia nigrescens, such that tree loss post‐drought was greater where elephants were present compared to where they were absent. Hence, our results suggest that species‐specific differences in drought resistance, as well as density‐dependent factors, likely impact the severity of drought effects on savanna tree communities. In savannas, drought has the potential to exert strong control on tree survival and prevent canopy closure, thus partially filling the role of megaherbivores in limiting large trees when these consumers are absent. As drought severity and frequency are predicted to increase in the future, the influence of drought on savanna vegetation structure becomes increasingly important to consider. Abstract : We compared changes in the number of large trees in African savannas with and without elephants before and after a severe drought. We found that both elephants and drought limited the abundance of large trees but not in an interactive manner. However, more trees of the dominant species, Senegalia nigrescens, were lost where elephants were present, suggesting species‐specific differences in response to drought and herbivory.